Nd:YAG 레이저를 이용한 철제유물의 표면부식물 제거 및 성분 변화 연구 - 이혜연; Hye Youn Lee; 조남철; Nam Chul Cho; 이종명; Jong Myoung Lee; 유재은; Jae Eun Yu (대한금속·재료학회지, 50(5), 2012)
The corrosion product of archaeological iron objects is supposed to be removed because it causes re-corrosion. So far it is removed by scapel and sand blaster but they depend on the skill and experience of a conservator and the glass-dust of the sand blaster is harmful to humans. Therefore this study applies a laser cleaning system which is used in various industrial cleaning processes, to remove corrosion product from archaeological iron objects. In addition, this work studies the alternation of corrosion product after laser irradiation, which evaluates the reliability of the laser cleaning system. Optical microscopy, SEM-EDS, XRD, Raman have been used to observe and analyse the surface of the objects. The results show the capacity of laser cleaning some corrosion product, but blackening appears with increasing pulses and laser energy, and some corrosion products, goethite and hematite, are partially altered to magnetite. These problems, blackening and alternation of corrosion product, should be solved by further studies which find the optimal laser irradiation condition and use a wetting agent.